Fine-scale hunting strategies in Australian fur seals - Salzeri, Perla; Luque, Sebastián P.; Arnould, John P. Y. (Frontiers in Marine Science, 2024)
Introduction Knowledge of the hunting strategies of top predators can provide insights into the cost-benefit trade-offs of their foraging activities. Air-breathing marine predators are constrained in their foraging activities due to their metabolic expenditure at depth being supported by limited body oxygen stores. Understanding how these species adapt their behaviours to maximise foraging success is of importance in view of the anticipated alterations to marine ecosystems in response to global change. The Australian fur seal (Arctocephalus pusillus doriferus), the largest fur seal species, has a distribution restricted to south-eastern Australia, which is one of the fastest warming oceanic regions and where the abundance, distribution and diversity of prey species is expected to change in coming decades. Methods In the present study, combined IMU (acceleration, magnetometer, gyroscope), depth and GPS data logger information was used to reconstruct 3-dimensional tracks during diving, assess energy expenditure and quantify prey capture events in adult female Australian fur seals during benthic foraging. Results The results revealed that individuals ascended at steeper pitches (to reduce transit time), remained for shorter durations and travelled shorter distances at the surface, and then descended at steeper pitches on subsequent dives after predatory events on the seafloor. Higher travel speeds and more directional changes during searching for prey along the seafloor, while requiring greater energy expenditure, were associated with more prey captures. Interestingly, individuals did not display conventional Area Restricted Search, with the heading between dives not influenced by prey encounters. Discussion Together, these results suggest Australian fur seals undertake rapid searching along the seafloor to surprise cryptic prey and, if prey is encountered, undertake rapid surfacing (to reload body oxygen stores) and return to nearby seafloor habitat with a similar but undisturbed prey field.